2004
DOI: 10.1080/00365540310018914
|View full text |Cite
|
Sign up to set email alerts
|

The effect of dietary fish oil on survival after infection with Klebsiella pneumoniae or Streptococcus pneumoniae

Abstract: Dietary fish oil is believed to have a beneficial effect in various infections and in autoimmune disorders. This effect may correspond to an altered immune response. In order to discover whether the effect of dietary fish oil is different in various infections, we studied the survival of mice fed fish oil or corn oil supplemented diets and infected in the lungs with either Klebsiella pneumoniae or Streptococcus pneumoniae. 120 NMRI mice were divided into 4 groups, of which 2 groups were fed a fish oil suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…In the present study, the group fed on Xaxseed oil for 4 weeks followed by infection with S. pneumoniae was not able to survive the infection. Our Wndings corroborate the observation made by Thors et al [16], who demonstrated the beneWcial eVect of dietary Wsh oil (10% w/w of the diet) on the survival of mice following induction of experimental pneumonia with Klebsiella pneumoniae, but not after infection with Streptococcus pneumoniae serotype 3 when supplemented for 6 weeks [16]. Interestingly, the group fed on Xaxseed oil for 9 weeks showed improved survival after infection with S. pneumoniae.…”
Section: Discussionsupporting
confidence: 93%
“…In the present study, the group fed on Xaxseed oil for 4 weeks followed by infection with S. pneumoniae was not able to survive the infection. Our Wndings corroborate the observation made by Thors et al [16], who demonstrated the beneWcial eVect of dietary Wsh oil (10% w/w of the diet) on the survival of mice following induction of experimental pneumonia with Klebsiella pneumoniae, but not after infection with Streptococcus pneumoniae serotype 3 when supplemented for 6 weeks [16]. Interestingly, the group fed on Xaxseed oil for 9 weeks showed improved survival after infection with S. pneumoniae.…”
Section: Discussionsupporting
confidence: 93%
“…Despite this, several studies have reported that an excess intake of n-3 polyunsaturated fatty acids may cause undesirable effects in both humans and animals, because they are able to reduce host immune resistance against infectious microorganisms (1,11). Thus, numerous investigations have indicated that diets containing n-3 polyunsaturated fatty acids enhance susceptibility to infection by Listeria monocytogenes (8,13,23), Salmonella enterica serovar Typhimurium (7), Mycobacterium tuberculosis (21), or Pseudomonas aeruginosa (22), whereas other recent observations have reported that these diets increase immune resistance against Klebsiella pneumoniae (2,3,27), although these effects could not be demonstrated in infection with Streptococcus pneumoniae (27). Therefore, it is possible that the consequences derived from the reduction of immune resistance by n-3 polyunsaturated fatty acids may also depend on the type of microorganisms and their pathogenic mechanisms.…”
mentioning
confidence: 96%
“…The severity of the acute pneumonia was also reduced. Moreover, survival among the mice fed fish oil for 6 weeks was better than among those fed a diet supplemented with corn oil [60]. Saini et al tested sea-cod oil contain- LA and ALA are converted to long chain PUFA sharing the same enzymatic pathway but this conversion is not complete and also variable with individuals.…”
Section: Animal Modelsmentioning
confidence: 99%